63.4k views
5 votes
Please help answer this question as soon as possible!

Please help answer this question as soon as possible!-example-1

1 Answer

7 votes

Answer:


a_(n) = 10.5 - 3n

Explanation:

The explicit rule for an arithmetic sequence is


a_(n) = a₁ + (n - 1)d

where a₁ is the first term and d the common difference

A recursive formula has the form


a_(n) =
a_(n-1) + d ( where d is the common difference )

Given


a_(n) =
a_(n-1) - 3 ⇒ d = - 3

Thus explicit rule with a₁ = 7.5 and d = - 3


a_(n) = 7.5 - 3(n - 1) = 7.5 - 3n + 3 = 10.5 - 3n

User Lesley
by
5.0k points